PENGARUH KUALITAS LAYANAN DAN BAURAN PEMASARAN TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS (Studi Kasus pada Astra Motor Weleri) - Gatot Ragil Saputro, 09.05.51.0035; ., Kunartinah (Students Journal of Economic and Management, 2013)
This study analyzes the relationship between service quality and customer satisfaction marketing mix in the form of customer loyalty. The object of this study is Astra Motor Weleri. Problems in the study refers to the phenomenon of the fall in sales of motorcycle dealers motorcycle astra Weleri significantly in March, August and September 2012. purpose of the study was formulated to examine factors - factors that affect customer loyalty.Models that were formulated in this study aims to provide a critical understanding of the concept and measurement of customer loyalty. Researchers incorporate elements of quality of services, marketing mix and customer satisfaction as the mediation and have significant consequences for customer loyalty. In addition to a theoretical modeling, this study has formulated five hypotheses. Purposive sampling method was chosen to obtain the required data in this study. The study used 84 respondents and all respondents were clients Astra Motor Weleri customers. Data analysis using regression analysis with SPSS.Test results showed that the f in say marketing mix, service quality and satisfaction with the same effect on customer loyalty. Test the hypothesis that all the variables have a positive and significant impact on customer satisfaction and loyalty. Multiple regression analysis of the quality of service expressed a greater effect on satisfaction in the appeal of the marketing mix, and satisfaction greater influence on loyalty than quality of service and the marketing mix. Test of mediation states that the indirect effect of service quality and greater marketing mix appeal direct effect, so the satisfaction of a mediating variable.The final conclusion of this study can be recommended as an input to management. Researchers believe that an approach that deals with dimensions of service quality and customer satisfaction can help managers improve customer loyalty, because the two most important veriabel to increase customer loyalty and customer satisfaction first must feel to be loyal.Key words: Quality Service, marketing mix, and Customer Satisfaction And Loyalty customers